Stock price determination in property sector companies - Anggela, S; Ariesa, Y; Gozali, R; Wati, R; Savitri, D (Technium Sustainability, 2022)
The purpose of this study was to examine whether the factors of ROA, NPM and DER affect the determination of stock prices in the property sector in 2015-2019. The research method approach uses deductive, quantitative types and descriptive properties. The number of property sector companies listed on the IDX are 58 companies and the sample that meets the criteria according to purposive sampling is 30 companies. Data analysis using the Structural Equation Model (SEM) with the Partial Least Square (PLS) approach model. PLS analysis was carried out with the help of SmartPLS 3.0 software. The conclusion from the results of this study shows that partially the analysis of stock price determination is only influenced by the ROA factor in a positive direction and NPM in a negative direction, while DER has no effect on the stock price. Simultaneously, the three factors of determination, namely ROA, NPM and DER, affect stock prices. The amount of this explanatory factor seen from the adjusted R2 value is 15.7% where the remaining 84.3% is explained by other variables that unresearched in this research.